Analisis Pengaruh Struktur Kepemilikan Terhadap Kebijakan Dividen dan Dampaknya Terhadap Nilai Perusahaan Sektor Barang Konsumsi Tahun 2019-2023 - Triyastiti Wulandari; Devi Permatasari; Zainal Alim Adiwijaya; Muhammad Ja’far Shodiq; Sri Dewi Wahyundaru (Jurnal Ilmiah Raflesia Akuntansi, 2025)
Abstrak— This study aims to analyze the effect of managerial ownership, institutional ownership, and dividend policy on firm value in the consumer goods industry sector listed on the IDX during 2019–2023. Firm value is important because it reflects performance and prospects that influence investment decisions. Ownership structure as an internal factor can affect firm value through supervision and incentives, while dividend policy, as measured by the dividend payout ratio (DPR), can be a signal of financial conditions to investors. This study uses a quantitative approach with a purposive sampling method and secondary data from annual financial reports. Data analysis was carried out using descriptive statistics and multiple linear regression, as well as classical assumption tests, F tests, t tests, and coefficients of determination. The results of the study indicate that managerial and institutional ownership have a significant effect on firm value, but do not have a significant effect on dividend policy. Dividend policy also does not have a significant effect on firm value. The limitation of this study is the low Adjusted R² value in the dividend policy model. Therefore, it is recommended that further research use a wider object and add financial ratio variables to obtain a more comprehensive understanding